Modeling of Wheat Production Under Irrigated and Rainfed Conditions Using the APEX Model in Arba Minch, Southern Ethiopia - Edmealem Temesgen Ebstu; Samuel Dagalo Hatiye; Demelash Wendmagegnehu Goshime (Advances in Agriculture)
Ethiopia’s reliance on wheat as a staple crop for sustenance and income is evident. Yet, its production is hindered by climate variations and management practices, notably in the Arba Minch area, in southern Ethiopia. This study utilizes the Agricultural Policy/Environmental eXtender (APEX) model to forecast irrigated and rainfed wheat yields in this area. Field surveys were carried out to collect yield data from wheat-producing kebeles. The APEX input data and information on climate, soil, and crop management practices were gathered from the Ethiopian Meteorological Institute, region, and district agriculture offices, respectively. The model accurately simulated wheat yields, showcasing sensitivity to climate, soil properties, and management practices. The model calibration and the validation result revealed good agreement between the observed and simulated yields in both irrigated and rainfed wheat farms, with statistical measures of NSE > 0.7, RSR ≤ 0.5, PBIAS ≤ ±10%, and R2 > 0.80). This study demonstrated the APEX model’s potential for simulating irrigated and rainfed wheat production in the study area. The finding of this study is valuable for agricultural planning and decision making, to increase wheat production in Ethiopia.